2013
DOI: 10.2310/8000.2013.130943
|View full text |Cite
|
Sign up to set email alerts
|

Reliability of the Canadian Triage and Acuity Scale: interrater and intrarater agreement from a community and an academic emergency department

Abstract: Objectives: The Canadian Triage and Acuity Scale (CTAS) is a five-level triage tool that is used to help prioritize the order in which emergency department (ED) patients should be seen. The objectives of this study were to determine the interrater and intrarater agreement of the 2008 CTAS guideline revisions by triage nurses and to compare agreement between triage nurses working in a small community ED and an academic ED. Methods: Seventy-eight triage nurses assigned CTAS scores and free-text presenting compla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
35
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(37 citation statements)
references
References 18 publications
1
35
0
Order By: Relevance
“…Due to the retrospective nature of the study design, we were unable to determine if CTAS scores were appropriately assigned for the patients in the study. Previous literature suggests that assignment of CTAS score has a good inter-rater reliability [24,25]. However, it is possible that ED crowding influenced assignment of CTAS score.…”
Section: Discussionmentioning
confidence: 99%
“…Due to the retrospective nature of the study design, we were unable to determine if CTAS scores were appropriately assigned for the patients in the study. Previous literature suggests that assignment of CTAS score has a good inter-rater reliability [24,25]. However, it is possible that ED crowding influenced assignment of CTAS score.…”
Section: Discussionmentioning
confidence: 99%
“…1,8 Fernandes et al reproduced a high level of agreement (κw = 0.79) between community and tertiary ED triage nurse scores on paper-based cases. 19 Grafstein et al showed that paired ED triage nurses observing a single clinical interaction could apply CTAS with similar levels of agreement in clinical practice (κw = 0.75). 15 Dong et al published a series of papers examining the interrater reliability of CTAS using eTRIAGE (an electronic CTAS decision support tool) and blinded triage nurse assessments, and demonstrated improved accuracy using electronic decision support compared to memory-or paper-based methods, 11 with good agreement between nursing scores (κw = 0.66) 10 and improvement in agreement with ongoing CTAS training.…”
Section: Discussionmentioning
confidence: 99%
“…Current evidence supports high levels of interrater reliability of CTAS between physicians, nurses, and paramedics, but has been limited to non-clinical, paper-based cases 5,8,19 or triage nurse agreement in an ED setting. [10][11][12]14,15 Two prospective comparisons of interrater reliability between paramedics and triage nurses published in abstract form described fair (κw = 0.37) to good (κw = 0.62) agreement.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, improved methodological design, including randomization and generation of sample size, will be possible in future experiments. Further areas that warrant investigation could include: comparing START to a mobile version of CTAS (such as Canadian Triage and Acuity Scale-Pre-Hospital and Emergency Department Versions, prn Education and Consulting) that does not require any fields to be populated with typing and is available on smart phone or tablet devises; comparing the non-MCI to MCI cases within the simulated patient (7,(6)(7)(8)(9) 6.5 (7,(4)(5)(6)(7)(8) (5)population to examine how the two triage tools compare to one another as this would provide some insight as to how a primary pre-hospital triage tool is at stratifying non-disaster patients; conducting prospective virtual or live simulations to compare these two systems; since triage nurses are in general unfamiliar with the START system one could imagine that with training the overall accuracy and time to triage could improve [5][6][7] when compared to CTAS; using a cross-over design when comparing the two systems could reduce the cofounding variable effects and decrease the sample size; or comparing a streamlined version of CTAS (as it is believed that in Ontario a pre-hospital CTAS version in under development) with START. Given that the goal of MCI triage remains the same when overtaxing of limited resources occurs, i.e., the greatest good for the greatest number, advocating for the use of either CTAS or START in the ED during a MCI may be reasonable, but choosing one over another is not justified from this investigation.…”
Section: Discussionmentioning
confidence: 99%
“…This lack of literature is surprising as ED triage systems, such as the CTAS, the Australian Triage Score, the Manchester Triage Score, or the Emergency Severity Index, are already highly integrated into ED culture throughout the world. 4 Given the well-established reliability, 5,6 validity, [7][8][9] and universal subscribership to the CTAS triage instrument within Canadian EDs, it would be appropriate to examine its use as a MCI triage tool in the ED context. Within Alberta, many hospitals will switch to START triage in the ED during a MCI.…”
Section: Background and Importancementioning
confidence: 99%